Therapy limitation in octogenarians in German intensive care units is associated with a longer length of stay and increased 30 days mortality: a prospective multicenter study - Bruno, Raphael Romano; Wernly, Bernhard; Beil, Michael; Muessig, Johanna M.; Rahmel, Tim; Graf, Tobias; Meybohm, Patrick; Schaller, Stefan J.; Allgäuer, Sebastian; Franz, Marcus; Westphal, Julian Georg; Barth, Eberhard; et al. (Journal of critical care, 2020)
Purpose - The approach to limit therapy in very old intensive care unit patients (VIPs) significantly differs between regions. The focus of this multicenter analysis is to illuminate, whether the Clinical Frailty Scale (CFS) is a suitable tool for risk stratification in VIPs admitted to intensive care units (ICUs) in Germany. Furthermore, this investigation elucidates the impact of therapeutic limitation on the length of stay and mortality in this setting. - Methods - German cohorts' data from two multinational studies (VIP-1, VIP-2) were combined. Univariate and multivariate logistic regression were used to evaluate associations with mortality. - Results - 415 acute VIPs were included. Frail VIPs (CFS > 4) were older (85 [IQR 82-88] vs. 83 [IQR 81-86] years p < .001) and suffered from an increased 30-day-mortality (43.4% versus 23.9%, p < .0001). CFS was an independent predictor of 30-day-mortality in a multivariate logistic regression model (aOR 1.23 95%CI 1.04-1.46 p = .02). Patients with any limitation of life-sustaining therapy had a significantly increased 30-day mortality (86% versus 16%, p < .001) and length of stay (144 [IQR 72-293] versus 96 [IQR 47.25-231.5] hours, p = .026). - Conclusion - In German ICUs, any limitation of life-sustaining therapy in VIPs is associated with a significantly increased ICU length of stay and mortality. CFS reliably predicts the outcome.